EMI CHALLENGES AND ISSUES IN SCIENCE CLASSROOM AT SECONDARY LEVEL- A SCENARIO IN ESL DOMAIN - Zaristan Khan; Zaheer Ullah; Ishrat Ranjhani (Policy Research Journal, 2025)
The use of English as a Medium of Instruction (EMI) in science classrooms at the secondary level presents unique challenges in English as Second Language (ESL) contexts. This study explores the multifaceted issues faced by both students and teachers in such settings. Key challenges include linguistic barriers that impede students’ comprehension of scientific concepts, limited proficiency among teachers in delivering content effectively in English, and the lack of culturally relevant and bilingual educational resources. Additionally, the complexity of scientific terminologies and language bias in assessments exacerbate these difficulties, often leading to reduced student participation, anxiety, and misconceptions. The research highlights the significant role of curriculum design, teacher training, and classroom interactions in addressing these challenges. Proposed strategies include the incorporation of bilingual materials, language scaffolding techniques, culturally relevant examples, and inclusive assessment practices. Emphasis is also placed on teacher professional development to enhance English proficiency and the adoption of interactive and technology-driven pedagogical methods. This study aims to provide insights into the critical areas that need attention to optimize EMI implementation in science education for ESL learners, fostering better engagement, understanding, and academic outcomes. The findings contribute to the broader discourse on effective teaching and learning practices in multilingual and multicultural educational environments.